2008
DOI: 10.1097/inf.0b013e31817109a4
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Among a Cohort of Human Immunodeficiency Virus Type 1-Infected and Uninfected Pregnant Women and Their Infants From Malawi, Zambia, and Tanzania

Abstract: Background: Morbidity and mortality patterns among pregnant women and their infants (before antiretroviral therapy was widely available) determines HIV-1 diagnostic, monitoring, and care interventions. Methods: Data from mothers and their infants enrolled in a trial of antibiotics to reduce mother-to-child-transmission of HIV-1 at 4 sub-Saharan African sites were analyzed. Women were enrolled during pregnancy and follow-up continued until the infants reached 12 months of age. We describe maternal and infant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
4
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 12 publications
6
74
4
2
Order By: Relevance
“…Cohort studies from other sub-Saharan countries have shown that, before the availability of ART, HEU children had a higher mortality risk than HIV-unexposed children [4,6,29]. However, reports on mortality in HEU and HIVunexposed children in the ARTera are scarce, and results are heterogeneous [19,[30][31][32][33]. Mortality rate in HEU children in this study (2.2 deaths per 100 live births per year at risk) was lower than that reported from other countries in sub-Saharan Africa in the ART era, though Cox proportional hazard models.…”
Section: Discussionmentioning
confidence: 86%
“…Cohort studies from other sub-Saharan countries have shown that, before the availability of ART, HEU children had a higher mortality risk than HIV-unexposed children [4,6,29]. However, reports on mortality in HEU and HIVunexposed children in the ARTera are scarce, and results are heterogeneous [19,[30][31][32][33]. Mortality rate in HEU children in this study (2.2 deaths per 100 live births per year at risk) was lower than that reported from other countries in sub-Saharan Africa in the ART era, though Cox proportional hazard models.…”
Section: Discussionmentioning
confidence: 86%
“…The report also estimated that the prevalence of HIV in pregnant women is over 30% in some countries of southern Africa. Approximately 2%-8% of pregnant women die of pregnancy-related illnesses in developing countries, partly because of HIV and malaria complications [11] and also due to lack of access to antiretroviral drugs (ARVs) [12]. Studies have reported that HIV patients with malaria have a higher frequency of symptomatic malaria and that malaria may increase HIV plasma viral load and decrease CD4+ T cells [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection in pregnancy has become the most common medical complication of pregnancy in some countries in sub-Saharan Africa [11]. It has been reported that over 70% of all HIV infections are a result of heterosexual contacts and that over 90% of infections in children come from mother-to-child transmission [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some differences exist between races, but these are more likely influenced by diet, menstrual status, sexual practices, socioeconomic status, and culture than host genetics. [7][8][9][10][11][12] The problems that women in the developed world perhaps view as most important, namely being able to conceive, avoid preterm labor and diabetes, and control the impact of infectious agents, are contrasted with those of resource-disadvantaged countries where women often die or suffer through violent acts, inadequate access to care, sexually transmitted infections including HIV, and their babies through birthing problems, malnutrition, and environmental challenges [13][14][15][16][17] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%